BAKTI SOSIAL BERSAMA JAMAAH MASJID JAMI NURUL YAQIN - Neng Asnawati; Siti Intan Hamidah; Yusuf Ismail (Institut Madani Nusantara, 2023)
Jami Nurul Yaqin Mosque is one of the mosques located in Cipelang district, Bogor that not only serves as a place of worship, but also has a role as a means of community interaction. Various activities can be done in the mosque, ranging from routine worship activities such as obligatory prayers, Jum'ah prayers to educational activities such as Ta'lim and equipped with facilities Education of children (Madrasah). But often the role of the mosque is not functioning optimally due to the availability of facilities and infrastructure. Therefore, the devotion activities focused on the procurement and optimization of facilities and infrastructure of Masjid Jami Nurul Yaqin include the procurement of mukena, cleaning equipment, and decoration of the madrasah study room. In addition, in the implementation of devotion also occurred interaction with the board of DKM and students of Madrasah Fatmah Hidayah. Interaction includes socialization activities and participate in teaching and learning activities. Steps taken in devotion include: (1) Provision of support facilities, (2) Optimization and maintenance of existing facilities, and (3) Interaction through involvement in the assembly.